CATETERISMO VESICAL FEMININO EM POSIÇÃO DE CONFORTO - Nair Matsuko Myamoto; Marilena Uratani; Iwa Keiko Aida; Diva Regina Battini Cesar (Associação Brasileira de Enfermagem, 1981)
It is an avaluation of the dorsal position with the legs stretched and separated, far away one from another, in the execution of thé feminine vesical catheterism.The informations that we have got show the facility of the execution, a lower danger of contamination, better physical and psychical comfort for the patient, besides a better stability.